Developing Students’ Interest In Learning English Through Digital Learning Platform - Joko Prayudha S (The Study Program of English Education of Palangka Raya University, 2023)
The implementation of technology in learning is a good way to help students understand learning material. Through an interesting strategy, it will encourage students to always improve their understanding related to the implementation of learning. This study aims to obtain information about the English digital learning platform used by teachers to be able to attract students' interest and motivation in learning in EFL classes. The research was carried out qualitatively through a descriptive approach. The informants in this study were three English teachers who provided teaching through the use of digital learning platforms. Data were obtained through observation of learning and interviews with teaching implementers. Then, the data analyzed through data reduction, data display and conclusions. The results of the study show that teachers use various digital learning platforms in teaching English in order to encourage students to increase their motivation in learning English. The digital learning platforms that are used are very diverse, such as Padlet, Youtube, Canva, Kahoot, Quizizz and so on. The teacher also explained that the use of digital learning platforms was able to positively increase students' understanding in mastering learning material.